2001
DOI: 10.1007/s001980170022
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Changes of Trabecular Architecture in Ovariectomized Rats Assessed by MicroCT

Abstract: To study the short- and long-term effects of estrogen deficiency on trabecular bone, three-dimensional measurements of proximal tibiae of ovariectomized rats were performed by micro-computed tomography (MicroCT). New three-dimensional (3D) techniques were employed to characterize the trabecular architecture from 0 to 110 days post-ovariectomy (OVX). These new methods no longer assume a plate or rod model of bone, but calculate trabecular thickness, separation, and number and their distribution by placing maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
115
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 37 publications
22
115
2
1
Order By: Relevance
“…This time point has been remarked as the early time point when major degenerative bone changes were found. 28,42,43 Recently, a study has elucidated that after 4 weeks of OVX (only 2 weeks after the injection of ZOL was started), the OVX group has shown the loss of the bone volume fraction in 64 %, whereas the OVX+ZOL group has shown the bone volume fraction similarly to the baseline. 34 In our study, we started to apply orthodontic force 4 weeks after OVX and we found almost the same results of both orthodontic tooth movement and OIRR in OVX+ZOL and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…This time point has been remarked as the early time point when major degenerative bone changes were found. 28,42,43 Recently, a study has elucidated that after 4 weeks of OVX (only 2 weeks after the injection of ZOL was started), the OVX group has shown the loss of the bone volume fraction in 64 %, whereas the OVX+ZOL group has shown the bone volume fraction similarly to the baseline. 34 In our study, we started to apply orthodontic force 4 weeks after OVX and we found almost the same results of both orthodontic tooth movement and OIRR in OVX+ZOL and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of interest with a length of 1·70 mm was placed in an axial direction in the secondary spongiosa of the distal femurs, just above the growth plate. Pixel dimensions were set at 2048 2048 170 longitudinally to expose the bone marrow (Laib et al 2000(Laib et al , 2001. Measured variables their abbreviations were as defined by Parfitt et al (1987).…”
Section: µCt Analysismentioning
confidence: 99%
“…7 Again, the general picture is that bone loss preferentially occurs due to loss of entire trabeculae. [8][9][10] Immediately after ovariectomy (OVX), bone remodeling accelerates and entire trabeculae are lost. 8 This initial phase of rapid bone loss is followed by a gradual decrease of bone mass, which is also observed in normally aging rats.…”
Section: Introductionmentioning
confidence: 99%